Dependence and manhood - Truby, Thomas L. (Journal of religion and health, 1982)
American culture is at best ambivalent and at worst hostile to the appropriateness of dependency in males. To reorient this cultural misconception, a healthful model of male dependency is needed-especially for health care and pastoral professionals. This paper offers such a construct by bringing the perspectives of a theologian, Dietrich Bonhoeffer, and a psychoanalyst, Heinz Kohut, to an examination of this issue. Out of this discussion, an ethic can be formulated which offers guidelines for the exercise of male dependency and a more complete model of manhood.